Molecular characterization of the promoter region of the Vascular Endothelial Growth Factor (VEGF) gene; Towards its involvement in susceptibility to obesity in Malay obese attributes - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Tengku Mohammad Ariff, Raja Hussin (2017)
The vascular endothelial growth factor (VEGF) gene at 6p12 encodes the VEGF protein which is a potent angiogenic factor and was first described as an essential growth factor for vascular endothelial cells. This protein was originally described as an endothelial cell-specific mitogen. VEGF plays a role in normal physiological functions such as haematopoiesis, bone formation, and wound healing. The activities of VEGF are unlimited to the vascular system; VEGF is produced by many cell types including platelets, macrophages, renal mesangial cells, keratinocytes, and tumour cells. It has been postulated to be the VEGF polymorphisms play a role in the integrated molecule between obesity and hypertension. This study aimed to perform molecular characterization of the human VEGF promoter region. The sequence of the promoter region of the human VEGF (Accession no. AF095785) was obtained from Gene bank. The open reading frames (ORFs), restrictions/methylation sites against a total of 560 recognition sequences, a total of three TATA boxes (TATA, tata, Goldberg Hogness Sequences) were identified using clustal X feature of VectorNTI. Transcriptional factors binding sites (TFBS) were identified using online tool. Promoter prediction was determined by doing manually matching of TFBS with TATA box from outward in. These manual findings were compared with online promoter prediction results.A total of 34 ORFs were identified, with a total of 20 on direct strand and 15 complementary strand. A total of 14vital restrictions sites were found against 560 recognition sequence in our database. Thirty eight TATA boxes inclusive of, 22 TATA (TATAA), 12 tata (TTGACA) and 4 Goldberg– Hogness (TATAAAA) sequences were identified. A total of 79 TFBS were identified using online tools. In the online promoter prediction program, prediction of transcription start site (TSS) was determined to be at -1562 bp and -562 bp. To the best of our knowledge this is the first study characterizing the molecular motifs and crucial elements within the reported promoter region of VEGF though successfully characterized in this study, there is a serious need to study the involvement of these motif in the transcriptional regulation of VEGF in future studies as per the role of these transcriptional factors in susceptibility to obesity and hypertension.